2004
DOI: 10.1158/0008-5472.can-03-3665
|View full text |Cite
|
Sign up to set email alerts
|

The Human Cervical Cancer Oncogene Protein Is a Biomarker for Human Hepatocellular Carcinoma

Abstract: Human cervical cancer oncogene (HCCR) was identified and appeared to function as a negative regulator of p53 gene. The objective of this study was to validate HCCR expression as a candidate marker for human hepatocellular carcinoma. HCCR epitope was identified as Y 355 LGTRR 360 . According to immunofluorescence study, HCCR was predominantly localized in the plasma membrane and cytoplasm of hepatocellular carcinoma. HCCR proteins were overexpressed in the tumorous compared with the nontumorous cirrhosis tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 30 publications
1
52
0
Order By: Relevance
“…Moreover, our study showed that AFP level was not correlated with early stage HCC lesions smaller than 3 cm (P=0.1148). This finding is consistent with the conclusions of other studies (27) demonstrating a lack of sensitivity of the AFP serological test when used in the screening for early tumors. While AFP had poor sensitivity in our study, it did show a high specificity for both HCC presence and early HCC in comparison to the low specificity of sCD25 in these analyses.…”
supporting
confidence: 93%
“…Moreover, our study showed that AFP level was not correlated with early stage HCC lesions smaller than 3 cm (P=0.1148). This finding is consistent with the conclusions of other studies (27) demonstrating a lack of sensitivity of the AFP serological test when used in the screening for early tumors. While AFP had poor sensitivity in our study, it did show a high specificity for both HCC presence and early HCC in comparison to the low specificity of sCD25 in these analyses.…”
supporting
confidence: 93%
“…The sensitivity and specificity of serum human cervical cancer oncogene (HCCR) at the cut-off value of 15 µg/mL in detecting HCC are 78.2% and 95.7%, respectively. Moreover, its sensitivities could achieve 76.9% in detecting HCC patients with seronegative for AFP and 69.2% in detecting HCC patients with tumor size less than 2 cm [58] .…”
Section: Genesmentioning
confidence: 99%
“…[3][4][5][6][7] The HCCR gene is classified into the two species HCCR-1 and HCCR-2 according to molecular characteristics. The HCCR2 is an alternative splicing form of HCCR1 and corresponds to amino acids 57-360 of HCCR1.…”
mentioning
confidence: 99%